Contribution of Abdominal Muscle Endurance and Leg Muscle Strength to Jump Height in Extracurricular Volleyball - Masrur, Muhammad; Fikri, Aprizal; Muslimin; Martinus; Wulandari, Pratiwi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to determine the contribution of abdominal muscle endurance and leg muscle strength to jump height in volleyball extracurricular in Senior High School (SMA) in Palembang. The method used in this study is a quantitative correlational method, involving 30 male and female volleyball athletes selected through purposive sampling. Abdominal muscle endurance was measured using a one-minute sit-up test, leg muscle strength was measured with a vertical jump and quadriceps dynamometer, while jump height was measured using a jump reach test commonly used in the performance assessment of volleyball athletes. Data were analyzed using multiple linear regression analysis to determine the simultaneous and partial contribution of independent variables to dependent variables. The results showed that abdominal muscle endurance and leg muscle strength together contributed significantly to jump height (R² = 0.687), explaining about 68.7% variation in jump ability. Individually, leg muscle strength contributed more (β = 0.542, p < 0.01) than abdominal muscle endurance (β = 0.312, p < 0.05). These findings suggest that both physical components are important for improving jump performance in high school volleyball athletes; However, the strength of the leg muscles has a more dominant role. It is recommended to coaches and health care teachers in Palembang to integrate an exercise program that emphasizes the development of core endurance and limb explosive energy in order to optimize sports performance in volleyball. This research contributes to understanding the biomechanical factors that affect volleyball-specific skills in adolescent athletes in educational settings.